The influence of human resources management practices and governmental support on organizational performance in small manufacturing businesses in Malaysia - Yusra Yaseen, Lazim (2015)
This study focuses on four knowledge fields (Human Resources Management, Employee Outcomes, Governmental Support, and Organizational Performance) which have been the center and attraction for many researches and studies. The growing awareness of the crucial role of human capital as the engine of organizations to sustain the competitive advantage, and the management of this worthy resource can lead to success. Pursuant to these facts, human resource management and governmental support are two of the most significant factors that considered having decisive influence on the organizational performance of small businesses. The main objectives of this study are: First, to assess the effect of human resources management practices on the organizational performance of small businesses through examining the causal order of the main variables (Human Resources Management, Employee Outcomes, and Organizational Performance) in an attempt to unfold the so-called “Black Box” to clarify the ambiguous relationship between human resources management practices and organizational performance; Second, to assess the vital contribution of governmental support to the organizational performance of small businesses. To achieve these objectives, a quantitative research study was conducted on a sample consist of 265 small businesses working in manufacturing sector/ Malaysia. Structural Equation Modelling with Amos 20 was used as an advanced quantitative measure beside other statistical measures in order to attain the prior objectives. The main findings of the study were; the existence of a significant relationship between human resources management practices as one “bundle” and organizational performance, and significant relationships between the component of employee outcomes (Trust in management, Cooperation, Intention to turnover, and Effort and involvement) and both human resources management practices and organizational performance. Also, there is a positive relationship between governmental support and organizational performance of small businesses